Survei Kepuasan Pelanggan Terhadap Layanan Service AC Menggunakan Metode Importance Performance Analysis (IPA) - Yumna Shafira; Ahmad Zakir; Andi Marwan Elhanafi (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
Consumer satisfaction is a major factor in the service and goods business sector. Efforts to determine consumer satisfaction at the level of performance in terms of service quality contained in PT. BEST is currently conducted through a consumer satisfaction survey. The survey was conducted manually and the form of the interview was not based on the criteria as a standard required for the uniformity of survey material, so it was difficult to carry out further analysis. Therefore, it is necessary to have a system to measure the level of customer satisfaction by applying an analytical method that considers the level of performance between the level of interest or expectations of the respondents. The purpose of this study is to apply the IPA method which is used to find out the attributes that need to be improved or reduced based on the location of the quadrant mapping. The result of this research is a system that is able to determine the level of customer satisfaction based on the level of performance and the level of importance as well as which attributes should be improved or reduced.